Modern creative methods of ballet staging and their reflection in the Kazakh ballet Zhusan - Aukhadiyev, Ilzat; Dosbatyrov, Daulet; Einasto, Heili (Creativity Studies, 2025)
The manuscript explores the evolution of ballet staging, focusing on the integration of modern dance and classical ballet. It traces this trend to the second half of the 20th century, highlighting the impact of modern dance’s flexibility on classical ballet’s rigidity, leading to a postmodern era in ballet theater. The study acknowledges significant Western European, American, and Russian researchers in ballet. It discusses how the fusion of classical ballet and modern dance has enriched choreography and led to innovative staging techniques. The manuscript examines the transformation in the definition of ballet, the rejection of strict genre boundaries, and the rise of individual authorial signatures in contemporary ballet productions. The work delves into the postmodernist quest for creative freedom, with choreographers like Merce Cunningham (1919–2009) seeking to break traditional dance constraints. It addresses contemporary ballet trends such as polystylism, eclecticism, collage, and complex performance structures. Focusing on Kazakhstan’s Zhusan ballet, the manuscript analyzes its choreography, music, and artistic interpretation. Zhusan exemplifies the fusion of classical, Kazakh, and contemporary dance, featuring a poetic libretto and a compilative score. In conclusions, the manuscript emphasizes the contemporary ballet’s shift towards the choreographer-director’s subjective vision, a departure from traditional approaches. This critical analysis offers a historical overview and examines the dynamic nature of ballet staging, showcasing a blend of tradition and innovation.